Molecular Basis of the Interaction of Salmonella with the Intestinal Mucosa - Darwin, K. Heran (American Society for Microbiology, 1999)
Salmonella is one of the most extensively characterized bacterial pathogens and is a leading cause of bacterial gastroenteritis. Despite this, we are only just beginning to understand at a molecular level how Salmonella interacts with its mammalian hosts to cause disease. Studies during the past decade on the genetic basis of virulence of Salmonella have significantly advanced our understanding of the molecular basis of the host-pathogen interaction, yet many questions remain. In this review, we focus on the interaction of enterocolitis-causing salmonellae with the intestinal mucosa, since this is the initiating step for most infections caused by Salmonella. Animal and in vitro cell culture models for the interaction of these bacteria with the intestinal epithelium are reviewed, along with the bacterial genes that are thought to affect this interaction. Lastly, recent studies on the response of epithelial cells to Salmonella infection and how this might promote diarrhea are discussed.